On Bounded Solutions of Some Classes of Two-Parameter Difference Equations in a Banach Space - Gorodnii, M. F.; Lagoda, O. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain criteria for the existence of bounded solutions of some classes of linear two-parameter difference equations with operator coefficients in a Banach space.